2018
DOI: 10.1108/mmms-03-2018-0041
|View full text |Cite
|
Sign up to set email alerts
|

Dual-phase-lag thermoelastic problem in finite cylindrical domain with relaxation time

Abstract: Purpose The purpose of this paper is to frame a dual-phase-lag model using the fractional theory of thermoelasticity with relaxation time. The generalized Fourier law of heat conduction based upon Tzou model that includes temperature gradient, the thermal displacement and two different translations of heat flux vector and temperature gradient has been used to formulate the heat conduction model. The microstructural interactions and corresponding thermal changes have been studied due to the involvement of relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Sur et al (2019) reported finite element analysis in a fiber-reinforced cylinder due to memory-dependent heat transfer. Mittal and Kulkarni (2018) considered thermoelastic problem in a finite cylindrical domain with the DPL model of thermoelasticity. Sharma et al (2011a) studied thermoelastic damping and frequency shift of vibrations in a transversely isotropic solid cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Sur et al (2019) reported finite element analysis in a fiber-reinforced cylinder due to memory-dependent heat transfer. Mittal and Kulkarni (2018) considered thermoelastic problem in a finite cylindrical domain with the DPL model of thermoelasticity. Sharma et al (2011a) studied thermoelastic damping and frequency shift of vibrations in a transversely isotropic solid cylinder.…”
Section: Introductionmentioning
confidence: 99%